Cyber-physical systems. - Sharma, Nonita; Sharma, Nonita; Awasthi, Lalit Kumar; Mangla, Monika; Sharma, K. P.; Kumar, Rohit (Boca Raton CRC Press, 2022)
"Cyber-Physical Systems: A Comprehensive Guide explores the complete system perspective, underlying theories, modelling, and the applications of Cyber Physical Systems (CPS). It aims to cover all topics ranging from discussion of rudiments of the system and efficient management to recent research challenges and issues. Editors aim to present the book in a self-sufficient manner and in order to achieve this, the book has been edited to include all the aspects of CPS. The book focuses on the concept map of CPS including latest technological interventions; issues, challenges, and the integration of CPS with IoT & Big Data Analytics. This aims to bring together unique contributions on cyber-physical systems research and education with applications in Industrial, Agriculture, and medical domains. The main aim of the book is to provide a roadmap to the latest advancements to provide optimal solutions in the field of CPS. The featured book aims to present the emergence of Cyber Physical Systems in response to revolutionary advancements in IoT. While discussing the associated challenges, the book also targets to devise efficient models which are competent to address these challenges. The book aims to cater to researchers and academicians working in the related field of CPS"--
Applications of artificial intelligence in cyber physical system / R. Sharma, N. Sharma -- Enhancement of healthcare sector and medical cyber-physical system with the help of Blockchain technology / A. Deshwal, S. Miglani -- Applications of cyber physical systems for industry 4.0 : a comprehensive review / Dr. Kirti Wanjale, Dr. Monika Mangla, Dr. A. V. Chitre.
Includes bibliographical references and index.
Keywords: Cooperating objects (Computer systems)